2020
DOI: 10.1080/09668136.2020.1749566
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalising Authoritarian Presidencies: Polymorphous Power and Russia’s Presidential Administration

Abstract: This article attempts to open up the 'black box' of the Russian Presidential Administration ('the Kremlin'). Borrowing from the literature on institutional presidencies and institutional approaches to authoritarianism, I argue that the administration institutionalised over the years of study, 1994-2012. More stable and predictable procedures enhanced administrative presidential powers but personalism and non-compliance with presidential orders remained. Original data on budget, staff, units, organisational str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…39 Between 2000 and 2012, only slightly more than half of all presidential assignments (porucheniia) were implemented by the respective addressees. 40 The 2012 May Decrees demonstrate a similar picture. But even when targets are formally met, the overarching aim of the indicators is often missed.…”
Section: The State Council Remains Dependent On the Presidencymentioning
confidence: 77%
See 1 more Smart Citation
“…39 Between 2000 and 2012, only slightly more than half of all presidential assignments (porucheniia) were implemented by the respective addressees. 40 The 2012 May Decrees demonstrate a similar picture. But even when targets are formally met, the overarching aim of the indicators is often missed.…”
Section: The State Council Remains Dependent On the Presidencymentioning
confidence: 77%
“…Lastly, while the tremendous accumulation of presidential power has enabled personalist authoritarian rule, it has also led to a paradox of governance: 9 While the presidency has accumulated more powers, state capacity has been weakened. Even the implementation of the President's own orders, such as national socioeconomic goals, remains patchy as long as they do not relate to core interests of Putin and the ruling elite itself.…”
Section: Russia's Paradox Of Governance: Strong Presidency-weak Capacitymentioning
confidence: 99%
“…Therefore, it was necessary to ensure the two leader samples that this paper analyzed were from leaders of state governmental systems which provide significant continuous or subject-variable international decision making authority to their heads. President Putin enjoys powers which many researchers have labeled as authoritarian, and unilateral decision-making capacity whose scope is largely determined by the president’s interpersonal relations with other members of the domestic government (Burkhardt, 2021; Dyson and Parent, 2017; and White, 2018). As a British Prime Minister, Major was appointed by the most majoritarian election system in Europe as well as able to hold influence over party members and ministries depending on his own personal ability to accrue executive authority (Brummer, 2016; Dowding, 2013; and Heffernan, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Prior to and in spite of data indicating that accurate LTA is likely limited to originally Englishlanguage texts, text coding studies have been conducted using translated speeches originally given in Russian. Such studies have demonstrated the lucrative potential of researching Russian state leaders due to their unilateral decision-making capacity in foreign policy matters and their large corpus of verbatim data (Burkhardt, 2021;Dyson and Parent, 2017;Hermann, 1980aHermann, , 1980band White, 2018). However, they have largely failed to ameliorate translation coding disparities between Russian and English.…”
Section: Lta and Russian Languagementioning
confidence: 99%
See 1 more Smart Citation